An analysis of Candlestick charting: the predictive power of the three-outside-up and three-outside-down Candlestick patterns in the context of small capitalization stocks in the USA - Hutton, Simon (Research of GSB, 2018)
This paper examines the predictive power of two Japanese Candlestick patterns for a 49-stock sample of small capitalization stocks drawn from the S&P 600 for the period 1 June 2005 to 15 May 2015. Using the normal approximation to the binomial for statistical testing and a dynamic holding period strategy to test the threeoutside- up and three-outside-down patterns, this study contradicts earlier works that used dynamic holding period strategies for large capitalization stocks and showed moderate levels of statistically significant predictive power. This study finds no statistically significant evidence of the predictive power of the three-outside-up and three-outside- down patterns for the sample and time period considered. Hence, the findings imply that there is no evidence to challenge the Efficient Market Hypothesis.